Nano‐gold micelles loaded Dox and Elacridar for reversing drug resistance of breast cancer - Liu‐Jing Wen; Yue‐Sheng Wang; Jie Zhang (IET Nanobiotechnology, 2023)
Abstract The aim of this study was to provide a new effective carrier for rescuing the sensitivity of drug‐resistant in breast cancer cells. Nano‐gold micelles loaded with Dox and Elacridar (FP‐ssD@A‐E) were chemically synthesised. With the increase in the amount of Dox and Elacridar, the encapsulation rate of FP‐ssD@A‐E gradually increased, and the drug loading rate gradually decreased. FP‐ss@A‐E had a sustained‐release effect. Dox, Elacridar, FP‐ss@AuNPs, and FP‐ssD@A‐E significantly improved cell apoptosis, in which, FP‐ssD@A‐E was the most significant. FP‐ssD@A‐E significantly decreased the cell viability and improved the Dox uptake. The levels of VEGFR‐1, P‐gp, IL‐6, and i‐NOS were significantly decreased after Dox, Dox + Elacridar, FP‐ss@AuNPs, and FP‐ssD@A‐E treatment. It was worth noting that FP‐ssD@A‐E had the most significant effects. The prepared FP‐ssD@A‐E micelles, which were spherical in shape, uniform in particle size distribution, and had good drug loading performance and encapsulation efficiency.